The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4161/adna.24019
|View full text |Cite
|
Sign up to set email alerts
|

Di-heterometalation of thiol-functionalized peptide nucleic acids

Abstract: As a proof-of-principle, two hetero-bimetallic PNA oligomers containing a ruthenium(II) polypyridyl and a cyclopentadienyl manganese tricarbonyl complex have been prepared by serial combination of solid-phase peptide coupling and in-solution thiol chemistry. Solid-phase N-terminus attachment of Ru(II)-polypyridyl carboxylic acid derivative, C1, onto the thiol-functionalized PNA backbone (H-a-a-g-t-c-t-g-c-linker-cys-NH 2) has been performed by standard peptide coupling method. As two parallel approaches, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…[329][330][331][332][333][334][335][336][337][338] However, while the synthesis of a number of Ru(II)-PNA conjugates has been reported, evaluation of their application in cells has yet to be investigated. [339][340][341] Please do not adjust margins Please do not adjust margins…”
Section: Ru-nucleotide Conjugatesmentioning
confidence: 99%
“…[329][330][331][332][333][334][335][336][337][338] However, while the synthesis of a number of Ru(II)-PNA conjugates has been reported, evaluation of their application in cells has yet to be investigated. [339][340][341] Please do not adjust margins Please do not adjust margins…”
Section: Ru-nucleotide Conjugatesmentioning
confidence: 99%
“…The reaction between thiol-containing biomolecules and chloroacetamide-containing reporters (and vice versa) has been investigated in an umber of independents tudies. [23] The reactionisu sually performed in aqueous/organic mixtures with an excess of 2t o1 0equivalents ao ne reactanto ver the other. The reactioni sa lso performed under reducing conditions (tris(2-carboxyethyl)phosphine (TCEP)) to prevent the formation of disulfides pecies.…”
Section: Synthesis Of Conjugatesmentioning
confidence: 99%
“…The SN2 reaction betweent hiol containingbiopolymers and reporters bearing iodoacetamide functions has been extensively reported in the past. [23] We hypothesized that such an SN2-thiol coupling reaction (TC) could be used along with OL and CuAAcf or the stepwise assembly of nucleic acid foldamers 2 from bifunctionnalized oligonucleotides and an adequately heterofunctionalized peptides caffold (Scheme 1). In the course of this work, we have found that the stepwise conjugation of oligonucleotide 3,b earing an aldehyde function at its 3' end, and oligonucleotide 4,b earing at hiol functiona ti ts 5' end, ontoc yclopeptide 6,f unctionalized with both an oxyamine and ac hloroacetamide moieties, allowed for the assembly of an intermediate conjugate 8 that may be subjected to intramolecular CuAAC reactions to form 2.A ll functionalities were found to be compatible and all ligations steps were performed with good to excellent yields.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, substitution with metal complexes have been of great interest to exploit additional properties of the new PNA-metal complex conjugate. 8,15,16,37,[44][45][46][47][48][49][50][51] In this work, we applied photoclick to achieve the insertion of a ferrocene moiety into a PNA sequence that was previously applied as an antisense agent on hepatitis B virus. 52 This sequence, which was synthesized via solid phase synthesis, 53 was further modified with the insertion of the PNA monomer bearing the modified tetrazole and a cysteine for conjugation via Michael addition (PNA, Fig.…”
Section: Pna Functionalization With Photoclickmentioning
confidence: 99%